Volume changes of the pancreatic head remnant after distal pancreatectomy - Klupp, Fee; Klauß, Miriam; Rahbari, Nuh Nabi; Felix, Klaus M.; Hinz, Ulf; Bergmann, Frank; Gaida, Matthias; Hackert, Thilo; Strobel, Oliver; Büchler, Markus W. (Surgery, 2020)
Background - Little is known about pancreatic regeneration in humans after surgical resection. We examined pancreatic head volume changes after distal pancreatectomy. - Methods - Using computed tomography or magnetic resonance imaging volumetry, we assessed volume changes of the pancreatic head remnant in 67 patients at defined time points (3, 6, 9, and 12 months) after distal pancreatectomy. A volume increase of >1 cm³ was defined as hypertrophy, a decrease of >1 cm³ as atrophy, and alterations of ±1 cm³ were considered as unchanged. Volumetry results were correlated with clinical patient data, histology, and immunohistochemistry for the pancreatic regeneration markers Pax4, Ghrelin, cholecystokinin receptor A, and cholecystokinin receptor B of the resection margin. - Results - Of 67 patients, 33 patients (49%) exhibited a hypertrophy of the pancreatic head remnant with a median increase of 5.08 cm³, 26 patients (39%) showed an atrophy, and in 8 patients (12%) pancreatic volume remained unchanged. No correlation of preoperative, postoperative, and new-onset diabetes with hypertrophy or atrophy was found. In patients with ductal adenocarcinoma, hypertrophy occurred less frequently compared to patients with other pathologies (38% vs 63%; P = .04). In patients with ductal adenocarcinoma, hypertrophy was associated with significantly shorter survival. Patients with a postoperative hypertrophy that did not suffer from ductal adenocarcinoma displayed significantly less fibrosis at the resection margin compared to patients with a postoperative atrophy and pancreatic ductal adenocarcinoma patients. Immunohistochemical staining revealed no differential expression of the tested regeneration markers in hypertrophy versus atrophy. - Conclusion - This study demonstrates volume changes of the pancreatic head remnant after distal pancreatectomy. Clinical and functional significance and underlying molecular mechanisms in humans remain unclear.
Available online 18 October 2019
Gesehen am 25.02.2020